1925 Haw. Sess. Laws 94, An Act to Prohibit the Use of Guns in the Taking or Killing of Fish and Providing Penalties For The Violation Of The Provisions Of This Act, Act 76, § 1 - (:unkn) unknown (General Publisher, 1925)
Prohibited to fish by means of any firearms.
--
Keywords: FISHING REGULATION